The Leverage of Administrative Regulation Practice on Public Freedoms in Algeria (Journal of Informatics Education and Research, 2026)
One of the pillars of the right and law state is that it grants freedom to individuals to do what they want - as a general principle. It is the right of individuals to enjoy their freedoms, especially the freedoms that cannot be dispensed with in their daily lives. But in the rule of law, too, their enjoyment of these freedoms is not attainable absolutely without restrictions or limitations. Therefore, it was necessary to control freedom so that it would not be misused according to the manner set by the law, and with the various guarantees established by the constitution to guarantee the rights of individuals on the one hand, and to ensure equality before the law and not to prejudice public order on the other hand, with what is called administrative regulation.